2017
DOI: 10.1080/10749357.2017.1368912
|View full text |Cite
|
Sign up to set email alerts
|

The Nottingham Fatigue After Stroke (NotFAST) study: results from follow-up six months after stroke

Abstract: Background Post-stroke fatigue is common and disabling. Objectives The aim of NotFAST was to examine factors associated with fatigue in stroke survivors without depression, six months after stroke. Methods Participants were recruited from four UK stroke units. Those with high levels of depressive symptoms (score ≥7 on Brief Assessment Schedule Depression Cards) or aphasia were excluded. Follow-up assessment was conducted at six months after stroke. They were assessed on the Fatigue Severity Scale, Rivermead Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…Although the exact mechanism is not clear, a previous study showed that higher self-efficacy is associated with proactive coping, 48 which may enable stroke survivors to better cope with fatigue. The correlation found between fatigue and depressive symptoms in this study was similar to those of previous studies, such as those conducted in Britain, 9 the Netherlands, 10 and Japan. 8 Ormstad and Eilertsen 4 have suggested that psychosocial and behavioral factors may play a role in the development of depression over time in stroke survivors with fatigue.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the exact mechanism is not clear, a previous study showed that higher self-efficacy is associated with proactive coping, 48 which may enable stroke survivors to better cope with fatigue. The correlation found between fatigue and depressive symptoms in this study was similar to those of previous studies, such as those conducted in Britain, 9 the Netherlands, 10 and Japan. 8 Ormstad and Eilertsen 4 have suggested that psychosocial and behavioral factors may play a role in the development of depression over time in stroke survivors with fatigue.…”
Section: Discussionsupporting
confidence: 92%
“…3 Fatigue can be sustained by psychosocial factors, 3,4 such as self-efficacy (r = −0.43 to −0.50), 5,6 which is a person's belief in his/her ability to control life's stressors, 7 and depressive symptoms (r = 0.21−0.61) in stroke survivors. [8][9][10] Fatigue exerts negative impacts on daily life, such as on instrumental activities of daily living, mobility, and social life. 11 Thus, alleviating fatigue is an important goal in clinical stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Balasooriya-Smeekens et al ’s study also alluded to the frequency of individuals experiencing fatigue after a stroke event, with over half of the forum users posting about occupation difficulties also pinpointing fatigue as an important factor. Recent research has examined factors associated with PSF and found reduced independence in activities of daily living and higher anxiety levels had a direct association with level of fatigue 27…”
Section: Discussionmentioning
confidence: 99%
“…This has led to calls for changes to practice so that patients receive much more intensive therapy during sub-acute stroke, and for trials to assess its effectiveness [2,8,9]. However, the emotional strain at this time after a stroke is severe [10] and the prevalence and severity of fatigue is increasingly recognised [11]. Therefore the prospect of participating in a trial which includes high repetition training, may feel daunting [12].…”
Section: Introductionmentioning
confidence: 99%